2017
DOI: 10.1093/ntr/ntx039
|View full text |Cite
|
Sign up to set email alerts
|

The 2016 Ferno Award Address: Three Things

Abstract: A lack of relevant research, and the likely prospect of significant clinical and public health benefit, underscore the importance of performing research on three topics related to smoking intervention: (1) researchers need to identify which contents of smoking counseling are effective; (2) researchers need to devise innovative strategies that use healthcare systems as conduits of smoking treatment delivery outside of clinical contacts; and (3) researchers need to use factorial designs to guide their developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…It is unclear why receipt of both components suppressed quit attempts. An advantage of the factorial experiment is that it can reveal such interactions; the causes of such interactions remain unclear (Baker, 2017;Baker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why receipt of both components suppressed quit attempts. An advantage of the factorial experiment is that it can reveal such interactions; the causes of such interactions remain unclear (Baker, 2017;Baker et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…of specific intervention components and using factorial designs to guide intervention development have been recognized as important but relatively neglected areas of smoking cessation research [15]. Only a few studies have reported using this approach to inform the development of DBCIs in other areas, e.g., to prevent substance use [16] and to reduce alcohol consumption [17].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the number of smokers interested in reduction treatment constituted only about 10% of all those asked about treatment interest in their clinic visits, typically only 5–10% of smokers will accept an offer to enter cessation treatment. 5,8,19,20 Moreover, of those smokers who were willing to reduce and were randomized to receive Motivation phase treatment, a meaningful portion (19%) opted to receive cessation treatment after receiving brief Motivation phase treatment. 3 …”
Section: Discussionmentioning
confidence: 99%
“…However, at any point in time, the great majority of smokers are unwilling to make a quit attempt. 38 Thus, most smokers leave health care visits without treatment for tobacco dependence. 810 …”
mentioning
confidence: 99%